Rethinking Management of Technology - Simatupang, Togar Mangihut (Jurnal Manajemen Teknologi, 2008)
This paper discusess how management of technology can be made more critical and a new method of reasoning is incorporated into this dicsipline to stimulate more widely application. Management of technology is found as a discipline that practitioners or academics need to have in order to be able to manage and improve technology. It relies on two streams of reasoning called deduction and induction. These two reasoning methods tends to neglect the human need to make sense and therefore fails to stimulate critical thinking of how to extract meaning from complex reality surrounding technology. It is suggested that abduction is the missing link in managemet of technology which is capable to combine the predominant strands of induction and deduction. Based on abductive thinking, TechnoValue is developed as a methodology to gain understanding the general statements when and how new technology creates value to all related stakeholders. Future research is also presented in this paper.Â Keywords:Â management of technology, induction, deduction, abduction, information technology